MEXICO IN THE MEMORIES OF THE SILVER AGE RUSSIAN POETS - IRINA Guseva (Ибероамериканские тетради)
The article touches upon the idea of common spiritual and intellectual values of the Russian and Mexi-can nations, of the mutual influence and mutual penetration of the cultures that leads to spiritual unity and better understanding between the representatives of different cultures and the idea of such mutual influence reflection in the language.